A wire-bond-less 10 KV SiC MOSFET power module with reduced common-mode noise and electric field - DiMarino, C.; Mouawad, Bassem; Skuriat, Robert; Li, Ke; Xu, L.; Johnson, Christopher Mark; Boroyevich, D. (2018)
While wide-bandgap devices offer many benefits, they also bring new challenges for designers. In particular, the new 10 kV silicon carbide (SiC) MOSFETs can switch higher voltages faster and with lower losses than silicon devices while also being smaller in size. These features can result in premature dielectric breakdown, higher voltage overshoots, high-frequency current and voltage oscillations, and greater electromagnetic interference. In order to mitigate these side effects and thus fully utilize the benefits of these unique devices, advanced module packaging is needed. This work proposes a power module package with a small footprint (68 mm × 83 mm), low gate- and power-loop inductances (4 nH), increased partial discharge inception voltage (53 %), and reduced common-mode current (90 %).